2008
DOI: 10.1111/j.1468-2494.2008.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritancy ranking of 31 cleansers in the Indian market in a 24‐h patch test

Abstract: Cleansing trends promise freshness, sensory and health benefits but may also be accompanied by an increase in soap-induced skin irritation. The aim of this study was to evaluate the irritant effect of 31 cleansers (28 bar soaps and 3 liquid cleansers) available in the Indian market. Eight percent w/v solutions of the soaps/cleansers were made and 30 microL of each of the solutions were applied to Finn chambers and occluded for 24 h along with distilled water (negative control) and 20% sodium dodecyl sulphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…All were acidic (pH < 7) rather than alkaline, in line with Lakshmi et al (2008) who found that alkaline soaps were more irritating than acidic soaps. All were acidic (pH < 7) rather than alkaline, in line with Lakshmi et al (2008) who found that alkaline soaps were more irritating than acidic soaps.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…All were acidic (pH < 7) rather than alkaline, in line with Lakshmi et al (2008) who found that alkaline soaps were more irritating than acidic soaps. All were acidic (pH < 7) rather than alkaline, in line with Lakshmi et al (2008) who found that alkaline soaps were more irritating than acidic soaps.…”
Section: Discussionsupporting
confidence: 73%
“…Supportive Care Guidelines Group (2005) define 'mild' soap as a non-scented, pH balanced product that does not contain lanolin. Lakshmi et al (2008) found that the least irritant soaps had a pH of 5 or 6 and suggested this is because skin pH is 5.5 and alkaline cleansers have a drying effect on the skin. Lakshmi et al (2008) found that the least irritant soaps had a pH of 5 or 6 and suggested this is because skin pH is 5.5 and alkaline cleansers have a drying effect on the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has compared the 31 cleansers available in the Indian market and has proven the above. [8]…”
Section: Cleanser Compositionmentioning
confidence: 99%
“…Irritant potential of soaps / cleansers in the Indian market, in a 24-hour patch test has been reported. [1] Sodium dodecyl sulfate (SDS) also known as sodium lauryl sulfate (SLS) is the most widely used chemical to study skin irritation in man. In our study, 20% SDS was included as the positive control.…”
Section: Introductionmentioning
confidence: 99%